PENDIDIKAN ISLAM MULTIKULTURAL SEBAGAI SOLUSI CYBERBULLYING PADA REMAJA - Thoriqul Huda; Syaiful Anwar; Sutiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Cyberbullying is a global issue where individuals use the internet to harass, humiliate, and harm others. A survey from 2022 showed that internet usage among 15-35-year-olds is a significant concern for young people. Cyberbullying often occurs when individuals engage in inappropriate behavior or engage in harmful actions. Multicultural education is crucial in addressing this issue, as it promotes inclusive learning environments without excluding cultural differences. The research method used is a cross-sectional study, which uses descriptive research methods and literature review. Data collected include questionnaires, pictures, and photographs, with the aim of analyzing and interpreting the data. The result from research is Cyberbullying is a harmful behavior that harms individuals by threatening, harassing, and causing harm through social media. It is a serious issue that requires attention and support from young people, parents, and the community. To combat cyberbullying, Indonesia needs to implement multicultural education, which aims to promote Indonesian islamic culture, including values, tolerance, respect, respect, and equitable.